[The frequency and profile of drug treatment in subjects with dyslipidemias and cardimetabolic diseases in an urban russian population older then 55 years] - Malyutina, S K; Mazdorova, E V; Shapkina, M Yu; Avdeeva, E M; Simonova, G I; Hubacek, J A; Bobak, M; Nikitin, Yu P; Ryabikov, A N (Kardiologija, 2021)
Aim To analyze frequency and profile of the lipid-lowering therapy (LLT) in patients with dyslipidemia (DLP) and cardiometabolic diseases (CMD) in a population sample aged 55-84 years at the current time (2015-2017).Material and methods Despite guidelines on DLP treatment and the availability of effective and safe lipid-lowering drugs, control of DPL in primary and secondary prevention of cardiovascular diseases (CVD) is insufficient. Knowledge of the level of pharmaceutical correction of DLP in the Russian population is limited; it requires an LLT assessment in various regions and in a wide age range, and a regular monitoring taking into account changing approaches to the correction of DLP. A random population of men and women aged 55-84 years (n=3 896) was evaluated in Novosibirsk in 2015-2017 (project HAPIEE). A joint DLP category was established as low-density lipoprotein cholesterol (LDL-C) ≥3.0 mmol/l, or total cholesterol (TC) ≥5.0 mmol/l, or triglycerides (TG) ≥1.7 mmol/l, or LLT. The combined group of DLP and CMD included ischemic heart disease (IHD), type 2 diabetes mellitus (DM2), and DLP. Regular LLD treatment for the recent 12 months, excluding the dosage of medicines, was assessed using the Anatomic Therapeutic Chemical (ATC) classification. The conditional control of serum lipids was taken as the achievement of LDL-C <3.0 mmol/l, TC <5.0 mmol/l, and TG <1.7 mmol/l.Results In the study sample, the total prevalence of DLP and CMD was 88 % (82.8 % for men and 91.3 % for women, p<0.001). 48.3% of patients in the IHD group, 35.0% in the DM2 group, 29.4% in the DLP group, and 32.8% in the CMD group took LLT. Control of serum lipids was achieved in 18.3% (37.9 % of patients on LLT) of patients with IHD; 9 % (25.6 % of patients on LLT) of patients with DM2; 7.3 % (24.8 % of patients on LLT) of patients with DLP; and 9.0 % (27.6 % of patients on LLTсреди) in the DLP and CMD group. Women with DM2 and DLP more frequently achieved lipid control than men (p<0.001). 98.7 % of study participants took statins as LLT.Conclusion In the sample of urban population aged 55-84 years in 2015-2017, 90 % of patients had DLP or CMD, and at least 3⁄4 of them required blood lipid control. The lipid control was achieved in every fifth IHD patient and in approximately 40% of those who took LLT. For DM2 or DLP patients, the lipid control was achieved in every tenth patient and in approximately 25% of those receiving LLT. Frequency of lipid control in IHD patients was comparable for men and women; in DM2 and DLP, men less frequently achieved the lipid control than women. About 70% of patients in the combined DLP and CMD group and more than 50% of IHD patients did not take LLT, which considerably contributed to the insufficient lipid control in primary and secondary prevention of atherosclerotic CVDs in this population.
Keywords: Diabetes Mellitus, Type 2; Hypolipidemic Agents; Female; dyslipidemie; léčivé přípravky; Dyslipidemias; Humans; ženské pohlaví; městské obyvatelstvo; mužské pohlaví; Male; lidé; diabetes mellitus 2. typu; hypolipidemika; Pharmaceutical Preparations; Urban Population